GAMBARAN PENGETAHUAN SISWA SISWI TERHADAP KEJADIAN DIABETES DI SD NEGERI NO. 106172 PANCUR BATU TUNTUNGAN - Nasution, Irfan Sazali; Hasibuan, Windi Fahriska; Husna, Haafizhah; Larasati, T Aida; Revaldo, Revaldo; Nabila, Nabila; Nuzlan, Divanada Rizki; Rezebri, Muhammad (Journal of Gender and Social Inclusion in Muslim Societies, 2024)
This study aimed to evaluate the effectiveness of school-based health education intervention in improving students' knowledge about diabetes. The research subjects were 5th and 6th grade students at SD Negeri No. 106172 Pancur Batu Tuntungan 2, with a total sample size of 47 people. The study used a quantitative descriptive design with a pre-test and post-test approach. Data were collected using a questionnaire covering the definition, symptoms, causes, and prevention of diabetes, and analyzed by descriptive statistics. The results showed a significant increase in the average score of students' knowledge from 63.93 in the pre-test to 85.62 in the post-test. This finding suggests that a school-based health education program can significantly improve students' health literacy. This intervention makes an important contribution in building students' awareness of chronic diseases, particularly diabetes. Although this study has limitations, such as the limited sample size and short duration of the study, the results provide a strong basis for the development of sustainable health education programs at the primary school level. It is recommended that future studies include a wider sample and utilize technology to support more interactive delivery.